Recepcja idei korczakowskich - Gulczyńska, Justyna (Biuletyn Historii Wychowania, 2012)
Janusz Korczak (the pen name of Henryk Goldszmit), writer, doctor, but above all one the best tutors and teachers. Korczak fought for improvement of children’s lives. By his life and convictions he tried to prove that a child is a complete human being, not only a person in the making. Struggling for human dignity of a child, he concentrated his efforts on three areas: dignity of children, the rights of children and their place in a society. We can learn his stance on the situation of children, in the context of the European Children’s Rights Movement at the beginning of the 20th century, when he says: „wzywam o magna charta libertatis, o prawa dziecka” – (“I call for Magna Charta Libertatis, for children’s rights”). The voice of Janusz Korczak in his famous pedagogical essay “Jak kochać dziecko” – (“How to Love a Child”) has retained its significance to the present day. Fighting for children’s rights, the “Old Doctor” (his second pseudonym) concentrated on the position of children in the adults’ world and their mutual relationships. That is why the analysis of the main spheres of activity of the adults and children (family, school, society) is so important today, and consequently, finding the answer to the questions: To what extent are the Korczak’s objectives in the abovementioned spheres realized today? How children’s rights are respected?